(untitled) (Research, Society and Development, 2022)
Homeopathy is a form of medicine that has been used since the middle of the 8th century, both for humans and for animals. Because of its benefits and lack of adverse reactions, it has also been expanded for use in the environment, through its use in plants and in the soil. It thus has the aims of ensuring wellbeing for all living beings and thinking of the health of the planet overall. This falls within the “one health” approach, which has the aim of promoting animal, human and environmental health. The objective of the present study was to demonstrate the use of homeopathy as a tool within one health. This was done through explaining the results and discussions of articles indexed over the last 10 years, with this use of homeopathic medicine in the three kingdoms of nature: mineral, vegetable and animal. The result was evidence of stability as well as the usefulness of ultra-diluted drugs as a unique health. Homeopathic science works on the welfare, treatment, and balance of nature, in order to repair every living being and prioritize health, totally within the “One Health” concept.